Tetramethylpyrazine ameliorates acute lung injury by regulating the Rac1/LIMK1 signaling pathway - Min, Simin; Tao, Weiting; Ding, Dushan; Zhang, Xiaonan; Zhao, Shidi; Zhang, Yong; Liu, Xiaojie; Gao, Kefei; Liu, Saisai; Li, Li; Hou, Min; Li, Yan (Frontiers in Pharmacology, 2023)
Acute lung injury (ALI) is a respiratory disorder characterized by severe inflammation of the alveoli and lung parenchyma. Tetramethylpyrazine (TMP), the main active compound in Ligusticum chuanxiong Hort (LC), can protect against lipopolysaccharide (LPS)-induced ALI. Our study aimed to investigate how TMP protects the endothelial cell barrier in pulmonary capillaries. We administered TMP intraperitoneally at different doses and found that acute lung injury in mice was improved, but not in a dose-dependent manner. TMP toxicity was tested in vitro. We observed that LPS-induced cytoskeletal remodeling was inhibited by TMP. Murine ALI was induced as follows: For the 1st hit, LPS (2 mg/kg) was injected intraperitoneally; after 16 hours, for the 2nd hit, LPS (4 mg/kg) was instilled intratracheally. The mice in treatment groups had TMP or dexamethasone administered intraperitoneally 30 minutes prior to the 1st hit and 30 minutes past the 2nd hit. Mice were euthanized 24 hours after the last injecting. We measured mRNA and protein levels using enzyme-linked immunosorbent assay (ELISA) and reverse transcriptase real-time PCR (RT-qPCR), respectively. The ultrastructural analysis was performed with transmission electron microscopy (TEM) and the cytoskeleton was observed by immunofluorescence. Immunohistochemistry and Western blotting were used to detect protein expression in the Rac1/LIMK1/ZO-1/Occludin signal pathway. The results showed that TMP treatment decreased inflammatory cell infiltration and alleviated LPS-induced damage in lung tissue. Also, TMP significantly inhibited the Rac1/LIMK1/ZO-1/Occludin signaling pathway. Our findings show that using TMP during sepsis can protect the pulmonary microvascular endothelial cell barrier and suppress inflammation. Therefore, TMP may have a promising therapeutic role in preventing acute lung injury from sepsis.